2011
DOI: 10.1088/0957-0233/22/12/125503
|View full text |Cite
|
Sign up to set email alerts
|

Wall temperature measurements using a thermal imaging camera with temperature-dependent emissivity corrections

Abstract: A methodology is presented whereby the relationship between temperature and emissivity for fused quartz has been used to correct the temperature values of a quartz impingement plate detected by an SC3000 thermal imaging camera. The methodology uses an iterative method using the initial temperature (obtained by assuming a constant emissivity) to find the emissivity values which are then put into the thermal imaging software and used to find the subsequent temperatures, which are used to find the emissivities, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Melendez et al [16] presented a way to overcome the problem of low spatial resolution in a harsh environment by using an infrared camera to study the composite plates exposed to fire. McDaid et al [17] presented a methodology whereby the relationship between temperature and emissivity for fused quartz was used to correct the temperature values of a quartz impingement plate detected by an SC3000 thermal imaging camera.…”
Section: Measurement Science and Technologymentioning
confidence: 99%
“…Melendez et al [16] presented a way to overcome the problem of low spatial resolution in a harsh environment by using an infrared camera to study the composite plates exposed to fire. McDaid et al [17] presented a methodology whereby the relationship between temperature and emissivity for fused quartz was used to correct the temperature values of a quartz impingement plate detected by an SC3000 thermal imaging camera.…”
Section: Measurement Science and Technologymentioning
confidence: 99%
“…Mcdaid [89] investigated the thermal inertia of a 10 mm thick steel plate and observed that at steady state conditions, the steel plate maintained its temperature. When the heat source was removed, the temperature changed by 1 0 C in approximately 20 seconds due to its high thermal inertia.…”
Section: Thermal Profilementioning
confidence: 99%
“…Thermal imaging has successfully found its place in research where non-intrusive and non-obstructive techniques are needed to study temperature and heattransfer based studies. McDaid[89], Lytle and Webb[90] have used thermal imaging to study heat transfer characteristics through thermal imaging[91][92][93]. Most studies investigated the non-impinged side of an object because thermal imaging systems failed to measure flame temperature accurately.…”
mentioning
confidence: 99%
“…The angular dependence of emissivity and infrared radiation were not tested in this work, but as mentioned in [132], between 30 o and 60 o there is a minimal discrepancy of less than 2%.…”
Section: Error Analysis Of Ir Measurementsmentioning
confidence: 96%